ULUR-ULUR TRADITION: Negotiations on Local Islam and Tulungagung Culture - Hendra Afiyanto; Mingyue Sun (Institut Agama Islam Negeri Ponorogo, 2024)
This study was made to construct the Ulur-Ulur tradition that emerged during the Majapahait period. The Ulur-Ulur tradition has passed through several periods of time, it is certainly interesting to study why it is still existence until now. The Ulur-Ulur tradition was still existence until the time of Islamic domination. What is the preservation of the Ulur-ulur tradition related to his ability to read discourse in each period? So that it has a different discourse in each period? or the existence of the Ulur-Ulur tradition due to the tolerance of the predominantly Islamic local community towards the previous culture? On the other hand, did the Ulur-Ulur tradition also negotiate itself from Islamic domination? This research uses historical and ethnographic methods. This study has three findings, first: the existence of the Ulur-Ulur tradition because of its ability to read discourse in each era, so that the Ulur-Ulur tradition has various meanings. Second, the tolerance of the majority Islamic community also maintains the existence of the Ulur-Ulur tradition. Third, the negotiation between the Ulur-ulur tradition and Islam, is also the key to the existence of tradition, the form of negotiation can be seen from the meaning of the offering.